Pengaruh Luas Pengungkapan Csr Terhadap Earning Response Coefficient Pada Industri High Profile Yang Terdaftar Di Pasar Modal - Eriandani, Rizky (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractThe study hypothesized that CSR disclosure strengthen the association between unexpected earning and abnormal return (ERC), since CSR disclosure provide more information to interpreting accounting earning. The sample of the study is annual report 2006 of the companies listed at the Indonesian Stock Exchange, and the company is the high profile industry. This finding raises the question of whether CSR information in annual report contain value-relevant about accounting earning or if investor are simply not capable of incorporating CSR information in the firm value estimates.